Child fever management: A comparative study of Australian parents with limited and functional health literacy. (16th October 2018) - Alqudah, Muahammad; Cowin, Leanne; George, Ajesh; Johnson, Maree
Abstract : Health literacy, or the ability to read and understand health information, is critical to the health of children. In this study, we compared the fever management knowledge of parents attending the emergency department with a child with fever. A cross‐sectional survey of 33 parents/carers with limited health literacy and 122 with functional health literacy was undertaken. There were no differences in the overall proportion of correct responses to knowledge or management questions posed by the two scales between the two groups. Both groups presented with limited knowledge and poor practices (<60% correct in both scales) in relation to fever knowledge and management in their children. Although health literacy impacts health utilization, we did not find any differences in these groups. Inappropriate practices, such as when to give medications, were evident. Educational programs, responsive to health literacy, are urgently needed to address these information needs for parents. An assessment of parents' health literacy level can guide the selection of information that can be easily read, understood, and acted upon to deliver the best health outcomes for children.